Contesting and Constructing International Perspectives in Global Education
VIII, 230 p.
Keywords: This volume addresses the need for an international perspective on global education, and provides alternate voices to the theme of global education. The editors asked international educators in different contexts to indicate how their own experience of global education addresses the broad and contested concepts associated with this notion. Following the lead of the internationally acknowledged authors from North America, Europe, Africa, Australia, and Asia, perspectives were provided on a wide variety of contexts including tertiary education, and teacher education; various pedagogies for global education, including digital pedagogies; and curriculum development at school, tertiary and community levels. Contesting and Constructing International Perspectives in Global Education explores the tensions inherent in discussions of global education from a number of facets including spatial, pedagogical, temporal, social and cultural; and provides critical, descriptive and values-laden interpretations. The book is divided into five sections, “Temporal and Spatial Views of Global Education”; “Telling National Stories of Global Education”; “Empowering Citizens for Global Education”; “Deconstructing Global Education”; and “Transforming Curricula for Global Education”. It is envisaged as a starting point for a stronger international conception of global education and a way to build a conversation for the future of global education in a neo-liberal and less internationally confident time.